Teicoplanin associated gene tcaA inactivation increases persister cell formation in Staphylococcus aureus - Habib, Gul; Gul, Haji; Ahmad, Prevez; Hayat, Azam; Rehman, Mujaddad Ur; Mohamed Moussa, Ihab; Elansary, Hosam O. (Frontiers in Microbiology, 2023)
Staphylococcus aureus is part of normal human flora and is widely associated with hospital-acquired bacteremia. S. aureus has shown a diverse array of resistance to environmental stresses and antibiotics. Methicillin-resistant S. aureus (MRSA) is on the high priority list of new antibiotics discovery and glycopeptides are considered the last drug of choice against MRSA. S. aureus has developed resistance against glycopeptides and the emergence of vancomycin-intermediate-resistant, vancomycin-resistant, and teicoplanin-resistant strains is globally reported. Teicoplanin-associated genes tcaR-tcaA-tcaB (tcaRAB) is known as the S. aureus glycopeptide resistance operon that is associated with glycopeptide resistance. Here, for the first time, the role of tcaRAB in S. aureus persister cells formation, and ΔtcaA dependent persisters’ ability to resuscitate the bacterial population was explored. We recovered a clinical strain of MRSA from a COVID-19 patient which showed a high level of resistance to teicoplanin, vancomycin, and methicillin. Whole genome RNA sequencing revealed that the tcaRAB operon expression was altered followed by high expression of glyS and sgtB. The RNA-seq data revealed a significant decrease in tcaA (p = 0.008) and tcaB (p = 0.04) expression while tcaR was not significantly altered. We knocked down tcaA, tcaB, and tcaR using CRISPR-dCas9 and the results showed that when tcaA was suppressed by dCas9, a significant increase was witnessed in persister cells while tcaB suppression did not induce persistence. The results were further evaluated by creating a tcaA mutant that showed ΔtcaA formed a significant increase in persisters in comparison to the wild type. Based on our findings, we concluded that tcaA is the gene that increases persister cells and glycopeptide resistance and could be a potential therapeutic target in S. aureus.